Prayer room design in transit area - Hamzah, Noor Hazwani; Rahayu Intan; Daud, Lutfi; Ismail, Sumarni; Utaberta, Nangkula; Mohd Yunus, Mohd. Yazid; ul Hussain, Mohd Amir; Nurshamiela (INSInet Publication, 2015)
The prayer room in transit area such as shopping mall, an exhibition hall,an airport,or other public building is an intervention to its surrounding and a welcoming place to find shelter or stop briefly, as a place of transit in our routine life. The prayer room does not merely provide physical presence to public place users in terms of anchoring and strengthening religious beliefs, it also provides an opportunity for spiritual presence. It is a location for religious activity that is not included in the construction plan. Thus, the prayer room is often placed in a vacant space in a building and is not integrated with other facilities. The conventional prayer room is a basic facility with improper arrangement. This type of prayer room were designed and constructed just to fulfil the requirements of the buildings only without any proper planning. Basically, this type of prayer room is inconvenient and uncomfortable for the user.This study; the scope will cover on the function and design of prayer areas or “musolla” in transit area. The designs were discussed in using qualitative method to make sure that the right and suitable aspects of design of the prayer room in transit area can be design and construct accordingly to the needs of the users. The effectiveness solutions for the prayer room will provide convenience and comfortable place as a transit area for the Muslim users to perform their prayer.